A high accuracy measurement circuit for soil moisture detection - Khan, Sheroz; Alam, A. H. M. Zahirul; Khalifa, Othman Omran; Islam, Md. Rafiqul; Zainudin, Zuraidah; Khan, Muzna S.; Muhamad Pauzi, Nurul Iman (World Academy of Science, Engineering and Technology (W A S E T), 2007)
The study of soil for agriculture purposes has remained the main focus of research since the beginning of civilization as humans’ food related requirements remained closely linked with the soil. The study of soil has generated an interest among the researchers for very similar other reasons including transmission, reflection and refraction of signals for deploying wireless underground sensor networks or for the monitoring of objects on (or in ) soil in the form of better understanding of soil electromagnetic characteristics properties. The moisture content has been very instrumental in such studies as it decides on the resistance of the soil, and hence the attenuation on signals traveling through soil or the attenuation the signals may suffer upon their impact on soil. This work is related testing and characterizing a measurement circuit meant for the detection of moisture level content in soil